Utilising Digital Badges in Higher Education. A Pilot Case Study Analysing their Influence on University Students - Federica Pelizzari; Simona Ferrari (Excellence and Innovation in Learning and Teaching)
The use of digital badges in education has gained popularity in recent years, offering a novel way to recognize and certify students’ competences and learning outcomes. These badges are akin to physical awards, but they can be shared online, making them accessible to potential employers and higher education institutions. A significant feature of digital badges is the detailed description of skills they represent, which enhances their transparency and value. Research has delved into the benefits and challenges of implementing digital badges, examining their impact on student motivation, learning, assessment, and best practices in design and implementation. Digital badges provide immediate feedback, thus promoting engagement and participation. They can also be “open” or “stackable,” motivating students to pursue long-term learning goals. However, the implementation of digital badges presents challenges. To ensure integrity, digital badges must have clear and reliable criteria, and stakeholders should validate their design. Good practices include student involvement in design, collaboration with industry experts, and the use of reliable technologies.